تدريس الشريعة في كليات القانون العراقية - د. قيس عبدالوهاب الحيالي; د. ندى سالم ملا علو (PROSPECTIVE RESEARCHES, 2023)
This research deals with the state of Sharia (Islamic Law) in the Colleges of Law in Iraq. It discusses the number of the teaching units in every stage and the curricula and the scientific level for the students. It also explores the effects of this situation on legislation. The research also tackles the importance of teaching Sharia in the Colleges of Law. The research presents also some possible solutions.